2009
DOI: 10.1111/j.1365-2133.2009.09276.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and childhood psoriasis

Abstract: References1 Cohen JS. Erythromelalgia: new theories and new therapies. J Am Acad Dermatol 2000; 43:841-7. 2 Rey J, Crétel E, Jean R, Durand JM. Erythromelalgia in a patient with idiopathic thrombocytopenic purpura. Br J Dermatol 2003; 148:177. 3 Newland A, Caulier MT, Kappers-Klunne M et al. An open-label, unit dose-finding study of AMG 531, a novel thrombopoiesis-stimulating peptibody, in patients with immune thrombocytopenic purpura. Br J Haematol 2006; 135:547-53. 4 Bussel JB, Kuter DJ, George JN et al. AMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 10 publications
3
54
1
4
Order By: Relevance
“…Cases with familial clustering tend to have an earlier age of onset (55,56), and one study has observed self-reported age of onset before 16 years in up to one-third of all psoriasis patients, though the finding has not been verified in population-based studies, such as the classic 1948 Faroese study (57). Interestingly, a recent study has confirmed a link between overweight and childhood-onset psoriasis (58). The assumption that being overweight precedes psoriasis is dependent on the presupposition that age of psoriasis onset in our study does not differ systematically from what has been previously reported.…”
Section: Discussionsupporting
confidence: 67%
“…Cases with familial clustering tend to have an earlier age of onset (55,56), and one study has observed self-reported age of onset before 16 years in up to one-third of all psoriasis patients, though the finding has not been verified in population-based studies, such as the classic 1948 Faroese study (57). Interestingly, a recent study has confirmed a link between overweight and childhood-onset psoriasis (58). The assumption that being overweight precedes psoriasis is dependent on the presupposition that age of psoriasis onset in our study does not differ systematically from what has been previously reported.…”
Section: Discussionsupporting
confidence: 67%
“…Studies of childhood psoriasis indicate an increased risk for metabolic co-morbidities (7)(8)(9)(10)35). In our material 13% of the children were overweight and 1.8% obese in the whole material according to the definition by Cole et al (25).…”
Section: Discussionmentioning
confidence: 55%
“…Studies of the paediatric and adolescent populations also suggest an increased risk for metabolic dysfunction (7)(8)(9)(10), but with no evidence that onset in childhood per se would predispose for overweight and cardio-metabolic comorbidity in adulthood (11,12). However, the difficult issue of causality has not been clarified and studies of body mass index (BMI) and lipoprotein profiles at onset of disease are lacking.…”
mentioning
confidence: 99%
“…15 Several studies have shown that patients with pediatric psoriasis in the United States and around the world have a higher prevalence of overweight and obesity compared with unaffected controls. 6,16 It is unclear whether being overweight or obese predisposes to psoriasis or affects the severity of disease in children, but a preliminary study noted overweight or obesity predated psoriasis by at least 2 years in 25 of 27 children. 17 It is hypothesized that having excess adipose tissue and an associated proinflammatory state with increased cytokine (eg, tumor necrosis factor [TNF]) expression, may predispose susceptible individuals to development of psoriasis.…”
Section: Methodsmentioning
confidence: 99%